Web-Based Expert System to Identify Pests and Diseases in Tomato Plants Using the Certainty Factor Method: Web-Based Expert System to Identify Pests and Diseases in Tomato Plants Using the Certainty Factor Method - Anggira Ganda Kusuma; Fauziah Fauziah; Endah Tri Handayani Esti (Institute of Computer Science (IOCS), 2020)
One of the important commodities for the domestic market such as are tomatoes, tomato has a comprehensive utilization of commodities, commodities tomatoes widely used for processing foods, to cosmetics. Therefore, the market demand for tomatoes to be very high. One cause of inhibiting the production of tomatoes is due to disease and pest attack, to resolve the issue dibutuhkanlah an expert in the field, but the number of experts is limited and can not help farmers simultaneously. To solve this problem we need a system that can handle the problem. The purpose of this study make the application of expert systems that will help farmers and communities in diagnosing diseases and pests on tomato plants. The system is web-based and using certainty factor. The results of using this system can provide a diagnosis in the form of a percentage based on the symptoms - symptoms that are selected by the user. This system has an accuracy value of 93%.